The effect of recurring drought conditions on anthocyanins biosynthesis of ‘Syrah’ grapes: a physiological, biochemical, and molecular approach - Antoniou, Chrystalla; Panagi, Eleni; Georgiadou, Egli C.; Gohari, Gholamreza; Panahirad, Sima; Theodorou, Nikolaos; Manganaris, George A.; Koundouras, Stefanos; Fotopoulos, Vasileios (My University, 2025)
Flavonoids constitute products of the secondary metabolism of higher plants and their biosynthesis is highly depended on an array of environmental stimuli, including water availability. Considering the critical role of anthocyanins and their plasticity in response to water deficit conditions in grapevines, the current study aimed to investigate the effect of drought stress on the regulation of seven biosynthetic genes (CHS2, CHI1, FLS1, DFR, ANR, LAR1 and UFGT) and a transcription factor (MybA1) implicated in their biosynthetic pathway. Analyses took place in one of the important grape cultivars (Vitis vinifera cv. ‘Syrah’) over seven successive on-vine developmental stages. In particular, vines (cv. ‘Syrah’ on 1103P rootstock) were subjected to two irrigation regimes (full irrigation: 100 % of crop evapotranspiration (ETc), and non-irrigated) starting at berry set, triplicated in randomized blocks for two consecutive years. Vine water relations were assessed through determination of stem water potential (ψs) and photosynthetic parameters. Results showed a negative effect of drought on ψs, stomatal conductance and net assimilation rate. Water scarcity led to increase of total sugar and anthocyanins content both growing seasons. Drought stress led to an induction of the genes implicated in flavonoid biosynthesis, evident at the full maturity stage, while LAR1 and MybA1 exhibited highly stable transcriptional profiles during the two successive growing seasons.
Keywords: Water deficit; Secondary metabolites; Vitis vinifera; Grape quality; Phenolic compounds; Anthocyanins